Transfer Pricing and Corporate Taxation Problems, Practical Implications and Proposed Solutions - King, Elizabeth (Springer New York : Imprint: Springer, 2009)
Transfer pricing is often identified as the most important tax issue that multinational corporations face. This publication is an extremely useful tool for practitioners and tax directors grappling with complex and contentious transfer pricing issues of various kinds. It contains a series of highly detailed case studies, which draw on the author's two decades as a government economist specializing in transfer pricing and valuation, a transfer pricing economist with Price Waterhouse, and, lastly, an independent consultant. These case studies elucidate the types of intercompany transactions that tax authorities often scrutinize, lay out how one should go about analyzing such transactions under the existing regulatory regime in considerable detail, and illustrate a number of proposed alternative approaches that could substantially reduce compliance costs and the frequency of transfer pricing disputes. Practitioners and tax directors will find the case studies extremely helpful in formulating defensible transfer pricing policies. The case studies may also be useful in assessing tax exposure attributable to intercompany pricing practices, as required under FASB Interpretation No. 48 (FIN 48). Tax policy analysts will find the evaluation and critique of existing methods and the development of alternative proposals thought-provoking and compelling. The book is divided into three parts: Part I contains a detailed review and critique of individual transfer pricing methods and the economic premises that underpin them. Part II contains a discussion of proposed alternative transfer pricing methods. Part III contains the aforementioned series of eight case studies, encompassing a broad range of transfer pricing issues. Global trading and certain types of Internet-based businesses, which the current transfer pricing regime does not adequately address, are among the issues covered. Each case study is analyzed under both the existing transfer pricing regime and one or more proposed methods.